ECMO and rigid bronchoscopy-assisted surgical resection of a giant pulmonary mesenchymal tumor in a child: a case report - Xinghui Xiong; Bin Du (BMC Pediatrics)
Abstract Background Giant pulmonary mesenchymal tumors in children pose significant challenges in pediatric anesthesia practice. During resection, these tumors can lead to complications such as cardiovascular collapse during anesthesia induction and injury to adjacent organs or blood vessels that may be compressed or displaced. Case presentation A 3-year-old girl presented to the pediatric clinic with cough, wheezing, and orthopnea (inability to lie flat due to dyspnea). After a diagnosis of giant pulmonary mesenchymal tumor, she underwent complete resection under extracorporeal membrane oxygenation (ECMO) and high-frequency ventilation, with rigid bronchoscopy used for airway management. ECMO was successfully discontinued, and the tracheal tube was extubated 3 days later. At 4-week follow-up, her symptoms significantly resolved, and no neurological or cardiovascular complications were reported. Conclusions This is one of the few detailed reports of a pediatric pulmonary mesenchymal tumor managed with ECMO and rigid bronchoscopy so far. Preoperative multidisciplinary cooperation, ECMO, and rigid bronchoscopy are critical for the successful resection of pediatric pulmonary mesenchymal tumors and may significantly improve long-term outcomes in pediatric patients.